Adaptasi Pagelaran Wayang di Era Digital: Ngamen Online Ki Yohan Susilo di Youtube - Shaffira Bella Shakinah; Ferry Adhi Dharma (Academic Journal of Da'wa and Communication, 2025)
This study aims to analyze the forms of adaptation in wayang performances as an effort to preserve culture and increase participation of the younger generation. The research method used was a qualitative approach, with data collected through interviews, observations of the “Online Busking” practice carried out by Ki Yohan Susilo via the “Langgeng Budaya” channel on YouTube, and a review of relevant literature. The findings of this study indicate that the use of digital media opens new opportunities for wayang to reach a wider audience without being bound by a specific space and time. The interaction pattern between the puppeteer and the audience has also shifted, as viewers can provide direct responses through available interactive features. Interestingly, some of the audience members are young people who previously had less involvement with wayang. This indicates that, to some extent, technology can help maintain the continuity of traditions without eliminating their fundamental values.